The Role of Brand Trust in Increasing the Influence of e-WOM and Hedonistic Lifestyle on Purchase Decisions for Used iPhone Devices: Peran Kepercayaan Merek dalam Meningkatkan Pengaruh e-WOM dan Gaya Hidup Hedonisme terhadap Keputusan Pembelian Gawai Bekas iPhone - Mahendri, Wisnu; Agustianingrum, Naning Farida (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
This study aims to analyze the role of brand trust in mediating the influence of electronic word of mouth (e-WOM) and hedonistic lifestyle on purchasing decisions for used iPhone devices. The study employed a quantitative approach and a survey method, selecting 150 students from KH. A. Wahab Hasbullah University through purposive sampling. Data were collected using a questionnaire and analyzed using structural equation modeling (SEM) based on partial least squares (PLS). The results showed that e-WOM did not have a direct effect on purchasing decisions but had an indirect effect through brand trust. Hedonistic lifestyle has a positive effect both directly and indirectly on purchasing decisions through brand trust. Brand trust proved to be an effective mediator in the relationship between e-WOM and hedonistic lifestyles in purchasing decisions. These findings imply that sellers of used iPhone devices need to focus their marketing strategies on building brand trust through effective online review management and considering hedonic aspects in their marketing strategies.